Analisis Pengaruh Kompetensi dan Beban Kerja terhadap Kinerja Perawat Kontrak Instalasi Rawat Inap di Rumah Sakit Bhayangkara H.S. Samsoeri Mertojoso Surabaya - Artanti, Yurika; Trigono, Ahdun; Rinaldi, Enrico Adhitya (Pusat Riset dan Inovasi Nasional, 2026)
The performance of contract nurses in hospital inpatient units is significantly influenced by individual competence and workload carried out during the execution of duties. Therefore, it is essential for hospital management to understand how these two factors impact nursing performance. This study aims to analyze the effect of competence and workload on the performance of contract nurses at the Inpatient Installation of Bhayangkara H.S Samsoeri Mertojoso Surabaya hospital. This research employed a quantitative approach using an analytical survey design. A total of 87 contract nurses were selected through simple random sampling, based on predetermined inclusion criteria. Data were collected using closed-ended Likert scale questionnaires and analyzed using multiple linear regression to determine the partial and simultaneous effects of the independent variables on performance. The results showed that competence had a significant effect on nurse performance (p = 0.002), as did workload (p = 0.000). Simultaneously, competence and workload contributed 33.8% to the variation in nurse performance (p < 0.05). These findings underscore the importance of continuous training programs and equitable workload management to improve the quality of nursing services. This study provides strategic recommendations for hospital human resource management, particularly in efforts to enhance service quality in inpatient care units.